CRYpuff / Anis Farhana Sabri and Noor Mardyana Ahmad Tarmizi - Sabri, Anis Farhana; Ahmad Tarmizi, Noor Mardyana (2023)
In this report, firstly, we introduced our business name, CRYpuff the Frozen Food, and other several information about our business. It includes our logo, mission and mission. The business we ventured for our assignment is under the Food and Beverage category. We established a partnership type of business, involving ourselves, Anis Farhana binti Sabri and Noor Mardyana binti Ahmad Tarmizi in order to strengthen our business. We also have attached our official MyENT registrations, SSM registrations and Go-ecommerce registrations. Furthermore, we established an online Facebook (FB) page to boost promote on our frozen curry puffs. We did a bit tease to the audiences about us and the products to excite them. We also attached our copywriting of hard sell and soft sell techniques. Soft sell is more to we promote our product to attract many potential customers to our product and business which means to let the audiences know about our start-up business. While hard sell is more give a push and give confidence to the customers who have interested to buy our products, only they need to do for last step is to contact us to purchase. Besides that, we acknowledge the fact that an entrepreneur must possess the entrepreneurial competencies for the business to run smoothly. The competencies can also encourage entrepreneurs to think various ways on how to overcome the obstacles in the business field. It astounded us how entrepreneurs could put those concepts into their daily life management. To simplify, as students, it was our pleasure to learn about the business field management and the entrepreneur way of thinking into solving problems while managing the franchises successfully. We conclude that entrepreneurship is a space for the community to build connection amongst each other and acknowledge the self-improvement needed.